(untitled) (Research, Society and Development, 2021)
In the Amazon, itinerant agriculture guarantees the subsistence of traditional communities, but causes intense environmental impacts. Forest restoration with the monitoring of indicators such as the seed bank is essential, as it provides information on species viable for germination in ecosystem disturbance scenarios. We aim, therefore, to evaluate the composition and density of the seed bank of a successional forest in the Amazon, subjected to the manipulation of water and nutrients for 12 years. The collections were carried out at random, with the aid of a hollow sampler, in a forest fragment with three treatments (control - CTL, litter removal - REM and periodic irrigation - IRR). We found 684 individuals and 32 species. The density of individuals ranged from 820 ± 112 to 972 ± 394 ind m-2 for REM and CTL, while that of species ranged from 188 ± 48 to 216 ± 9.24 spp m-2 for CTL and REM, respectively. The bushes had the largest number of emergent individuals, and the vines, the smallest. The highest Shannon-Weanver and Pielou indices were observed in the CTL. The species Vismia guianensis, Cecropia obtusa and Cyperus rotundus were the most frequent in all treatments and the pioneer species predominated. The emergence speed of the REM treatment was lower than the CTL, while the average emergence time was similar between treatments. The composition and density of the seed bank were not affected by the residual effect of litter handling. Despite this, results were slightly higher for CTL treatment.